ANALISIS KECELAKAAN KERJA DENGAN MENGGUNAKAN METODE HAZARD AND OPERABILITY STUDY (HAZOP) (Studi Kasus: PT. XYZ) - Muhammad Nur (Jurnal Teknik Industri Terintegrasi, 2019)
PT. XYZ is a registered company that provides business in the provision and services of national construction in Indonesia. Established in 1997, he continues to perform reliable services for many domestic and international clients. With its rank in Riau Province, Indonesia, SGJ participates in the development of major infrastructures in the province and in particular, has deep experience in construction and maintenance in the oil and Gas industry. PT. XYZ is located in the CS RUR B MINAS AREA, Minas Jaya, Minas, Siak Regency, Riau province. As for the problems that exist during the exercise work is: 1) The lack of awareness of workers in the importance of occupational health and Safety (K3) in the working environment of PT. XYZ. From the existing problem, the repair solution offered is: 1) Implementing the 5S method in the work, 2) adding air circulation and indoor lighting Workplace, 3) establishing facilities in a work area such as Stand, 4) give signs or symbols Work area, 5) Provide K3 training on the use of APD, 6) Create worksheets in the use of APD in the work area.